Cape Espenberg Birnirk Project (CEBP) faunal material summary analysis (2016-2019) - Lauren Norman; Dennis O'Rourke (Arctic Data Center, 2020)
This research brings together researchers and community members to develop a deeper and broader understanding of the Birnirk archaeological complex and its contribution to the emergence of the Inupiat culture. Using archaeological, genetic, and environmental data sets, project participants examine the question of a cultural break around AD 1000 in northwest Alaska and the implications for later cultural development in the region. This dataset provides summary statistics for a sample of the faunal material collected from two seasons of excavation of an early Thule house and a Birnirk house. The main goal of the faunal analysis is to test the hypothesis that Birnirk people used the environment and animal resources in different ways than later Thule Inuit. These changes are explored in relation to the larger cultural and environmental contexts of changing climate, ecology, technology, interaction, and social organization reconstructed in collaboration with the other analyses in this collaborative project.